2022
DOI: 10.1186/s12913-022-07603-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of accreditation on health care services performance in Kiryandongo district, Uganda: a longitudinal study

Abstract: Background The COVID-19 pandemic has emphasised the need for quality laboratory services worldwide. There is renewed focus to strengthen country capacities and laboratories to effectively respond to public health emergencies and patient outcomes. Uganda launched the accreditation program for public health facilities in 2016 with sixteen laboratories. As of June 2021, twenty-three public laboratories have attained ISO 15189:2012 accreditation status. Despite the tremendous achievements of accred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Numerous medical laboratories that have met the standard’s requirements and received accreditation have shown improvements in the quality of medical services and patient safety. 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…Numerous medical laboratories that have met the standard’s requirements and received accreditation have shown improvements in the quality of medical services and patient safety. 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…These standards require establishing and adhering to clear administrative and clinical practices that establish clear standards and encourage information exchange and staff and/or patient issue resolution. Studies have shown that such standards support the development of a "culture of quality" and motivate personnel to perform to the best of their abilities [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Staff ongoing education, staff wellbeing promotion, use of evidence-based practices, internal and external coordination, risk management, staff and patient safety, etc., are part of the IEEA requirements. Accordingly, emergency preparedness, in general, is a core element of the accreditation standards [5,10,12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient satisfaction is something that must be maintained by a hospital or health clinic so that the image of the service can remain of high quality and its existence can continue to survive in society (Lee & Lee, 2022;Li et al, 2022). Patient satisfaction is a global indicator of a health service accreditation standard (Organization, 2022), without patient satisfaction, it cannot be ascertained whether a health service is of good standing (Matovu et al, 2022). The increasing number of patients who are satisfied with a health service means that the service provided by a hospital or health clinic is good or very good (Mohan, 2023).…”
Section: Introductionmentioning
confidence: 99%